Persuading Aristotle The Timeless Art of Persuasion in Business Negotiation and the Media - Thompson, Peter (Allen & Unwin, 2014)
Using principles introduced by Aristotle and refined ever since, the author of this text seeks to provide the reader with the key to effective communication. To persuade you must use "ethos", "logos" and "pathos"; in demanding face-to-face situations, Thompson shows how